Epidermolytic Hyperkeratosis in an Epidermoid (Infundibular) Cyst. (March 2022) - Prestwood, Courtney A.; Vandergriff, Travis
Abstract : Abstract: Epidermolytic hyperkeratosis (EHK) is an uncommon histopathologic reaction pattern that may represent a primary pathological process or a coincidental finding in a variety of neoplasms. We present a case of EHK in an epidermoid (infundibular) cyst. Histopathologically, EHK demonstrates vacuolar degeneration of keratinocytes in the spinous and granular cell layers, with disrupted cellular boundaries, enlarged basophilic keratohyalin-like granules and amorphous eosinophilic inclusions, along with massive hyperkeratosis. In addition to the morphologic description of EHK, we summarize the diagnoses in which EHK has been reported. Prior cases of EHK in an epidermoid (infundibular) cyst are summarized to compare findings. The significance of incidental EHK in skin lesions is unknown.